Understanding depolymerization kinetics of poly(butyl methacrylate) using flow chemistry - Göhringer, Leonard; Ammini, Gayathri Dev; Junkers, Tanja (Faraday discussions, 2026)
Reversible addition-fragmentation chain-transfer (RAFT) depolymerization offers a promising and (comparatively) low-temperature chemical recycling strategy, enabling high yields of recovery of monomers. Conducting this process under continuous flow conditions, in combination with an inline dialysis set-up was recently demonstrated to accelerate depolymerization. However, several kinetic aspects of the process remain poorly understood, complicating the optimization of flow processes. In this study, we determined the kinetics of RAFT depolymerization under continuous flow conditions on the example of poly(butyl methacrylate), polyBMA. Depolymerizations were followed at temperatures from 120 °C to 160 °C, and the activation energy of the process was determined to be 79.5 kJ mol−1. Further, a square root dependence of the rate on the initial polymer concentration was determined. Comparison of the rates of depolymerization with clearance rates during in-flow membrane dialysis showed that the dialysis process is, by a large margin, the rate-determining step in the entire process. Removal of monomer was accelerated by increasing the cross-flow rate in the dialysis, providing a first step towards optimal conditions in the flow depolymerization.
Veröffentlicht: 06 June 2025
Gesehen am 16.01.2026